2014
DOI: 10.1074/jbc.m113.511964
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Secreted Adipokine WNT1-inducible Signaling Pathway Protein 2 (WISP2) Is a Mesenchymal Cell Activator of Canonical WNT

Abstract: Background: WISP2 is a cytosolic and secreted protein produced by precursor cells. Results: Secreted, but not cytosolic, WISP2 activates canonical WNT and prevents adipogenic differentiation. Conclusion: WISP2 is an important regulator of both adipogenic commitment and differentiation. Significance: Secreted WISP2 is a novel regulator of canonical WNT and PPAR␥ activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 35 publications
(53 reference statements)
5
66
0
Order By: Relevance
“…However, CCN5 knockout mice have not been generated to date. Grunberg et al [32] have reported that CCN5 functions as an adipokine to activate canonical Wnt signaling and regulate adipogenic commitment. In our study, CCN5 was sparsely detected in OA and RA cartilage and was expressed to a greater extent in the synoviums of OA and RA than in the normal hip.…”
Section: Discussionmentioning
confidence: 99%
“…However, CCN5 knockout mice have not been generated to date. Grunberg et al [32] have reported that CCN5 functions as an adipokine to activate canonical Wnt signaling and regulate adipogenic commitment. In our study, CCN5 was sparsely detected in OA and RA cartilage and was expressed to a greater extent in the synoviums of OA and RA than in the normal hip.…”
Section: Discussionmentioning
confidence: 99%
“…We exploited the responsiveness of homeostatic heart tissue to WNT-974 exposure to identify Wnt-regulated cellular processes that may suppress CM cell cycle reentry. Tissues exposed to WNT-974 exhibit a significant change in expression of genes that contribute to remodeling of the extracellular matrix (ECM), including several that are associated with Wnt/β-catenin signaling (14,(19)(20)(21) (Fig. 2A and Dataset S1).…”
Section: Resultsmentioning
confidence: 99%
“…12 In contrast, impaired recruitment and differentiation of precursors into mature adipose cells through WNT1-inducible-signaling pathway protein 2 (WISP2) has emerged as a limitation for adipogenesis, rather than mature adipose cell malfunction. 17 There is a definite need for establishing methods to quantitatively describe adipose tissue cellularity, and the mathematical study presented herein of adipose cell adaptions in a shortterm HFD mouse model may serve as a useful framework to validate different hypotheses of adipose cell function and energy storage capacity.…”
Section: Discussionmentioning
confidence: 99%